Synthesis of 4-Acetamido-4-deoxy-β-d-quinovose Containing Branched Pentasaccharide Corresponding to the Cell Wall O-antigen of Acinetobacter baumannii Strain 9 - Bag, Puja; Sahaji, Samim; Misra, Anup Kumar (Synthesis, 2025)
A convenient strategy has been developed for the synthesis of a branched pentasaccharide containing a rare sugar, 4-acetamido-4-deoxy-β-d-quinovose, corresponding to the cell wall O-antigen of Acinetobacter baumannii strain 9 in very good yield. The desired pentasaccharide has been achieved as a fully deprotected form enabling the scope for the conjugation with an appropriate aglycone or protein. The constructions of 1,2-cis glycosyl linkages between the d-galactosamine and d-glucose moieties in the molecule were achieved using thioglycosides as glycosyl donors under iodonium ion–promoted glycosylation conditions in an ether-based solvent.
Keywords: Carbohydrates; Glycosylation; Glycosides; Oligosaccharides; Total synthesis; Acinetobacter baumannii